ANALISIS SENSE, FEEL, THINK, ACT DAN PENGARUHNYA TERHADAP LOYALITAS PELANGGAN DI FRONT OFFICE HOTEL OPI INDAH, BANYUASIN - Hariman; Permatasari, Mustika; Putri, Vania Okky; Anggarini, Meisya; Taslim, Taslim (Program Studi Manajemen Divisi Kamar, 2025)
This study investigates the influence of experiential marketing dimensions (sense, feel, think, and act) on customer loyalty at the front office service of Opi Indah Hotel Banyuasin, a mid-scale hotel in a non-metropolitan area of Indonesia. Motivated by the lack of empirical studies in local hotel contexts, this research applies a quantitative method using purposive sampling to survey 35 guests. Data were collected through Likert-scale questionnaires and brief interviews, and analyzed using multiple linear regression via SPSS. The findings reveal that all four experiential marketing dimensions significantly and positively affect customer loyalty, both partially and simultaneously. Among them, the think dimension emerged as the most influential, highlighting the importance of rational factors such as service speed, cleanliness, and price fairness. The model explains 95.1% of the variance in customer loyalty, supporting the validity of the Strategic Experiential Modules (SEM) framework in a local hospitality context. This research contributes to both theory and practice by expanding the geographical applicability of experiential marketing and providing insights for service strategy development in regional hotels.